Activation of SK/KCa Channel Attenuates Spinal Cord Ischemia-Reperfusion Injury via Anti-oxidative Activity and Inhibition of Mitochondrial Dysfunction in Rabbits - Zhu, Jie; Yang, Li-Kun; Chen, Wei-Liang; Lin, Wei; Wang, Yu-Hai; Chen, Tao (Frontiers in Pharmacology, 2019)
Spinal cord ischemia-reperfusion injury (SCI/R) is a rare but devastating disorder with a poor prognosis. Small conductance calcium-activated K+ (SK/KCa) channels are a family of voltage-independent potassium channels that are shown to participate in the pathological process of several neurological disorders. The aim of this study was to investigate the role of SK/KCa channels in experimental SCI/R in rabbits. The expression of SK/KCa1 protein significantly decreased in both cytoplasm and mitochondria in spinal cord tissues after SCI/R. Treatment with 2 mg/kg NS309, a pharmacological activator for SK/KCa channel, attenuated SCI/R-induced neuronal loss, spinal cord edema and neurological dysfunction. These effects were still observed when the administration was delayed by 6 h after SCI/R initiation. NS309 decreased the levels of oxidative products and promoted activities of antioxidant enzymes in both serum and spinal cord tissues. The results of ELISA assay showed that NS309 markedly decreased levels of pro-inflammatory cytokines while increased anti-inflammatory cytokines levels after SCI/R. In addition, treatment with NS309 was shown to preserve mitochondrial respiratory complexes activities and enhance mitochondrial biogenesis. The results of western blot analysis showed that NS309 differentially regulated the expression of mitochondrial dynamic proteins. In summary, our results demonstrated that the SK/KCa channel activator NS309 protects against SCI/R via anti-oxidative activity and inhibition of mitochondrial dysfunction, indicating a therapeutic potential of NS309 for SCI/R.